STRATEGI KEPALA SEKOLAH PEREMPUAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Wulandari, Yeni; Dwi Sartika, Eva; Perawati, Perawati (Graduate Program Magister Manajemen Pendidikan, 2018)
This study aimed at describing the leadership strategy of women principal. This research was done in SD Negeri Kota Palembang 116. The approach used in this research was a case study. Results of the study in improving the quality of education in SD Negeri 116 Palembang include a good personal approach with all stakeholders of the school; planning the school with the greatest extent possible, analyze the challenges, barriers and opportunities in the future; establish good cooperation with all educators, empowering educational effort through cooperation, provide an opportunity to improve educators’ practices, and encourage the involvement of the educators on supporting the programs of the school. The results implied the teachers to maximize the existing facilities and infrastructure to maximize the learning process, and the school has had a strong culture.